Analysis of Information and Communications Technologies Adoption by Small and Medium-Sized Enterprises in Kogi State - Zakariya, Nurudeen Yakubu; Aduku, Danlami Joseph; Aduku, Martha Lami (Journal of Asian Business Strategy, 2019)
This study focused on Information and Communications Technologies (ICT) adoption by Small and Medium-sized Enterprises in Kogi State. The study determined the constraints against the adoption of ICT by SMEs in Kogi State. This study used survey research design. The population of the study comprised of 2027 SMEs. Multi-stage sampling technique was used to choose the required sample size of 323. Descriptive statistics and Binary Logit Regression were used for analysis. Findings show that excessive reliance on foreign technology, unreliability of e-commerce systems, high costs of ICT equipment, insecurity and legal and regulatory issues has significant influence on the adoption of ICT by SMEs in Kogi State. The study concluded that despite the benefits of ICT, some constraints detract its adoption by SME owners in Kogi State. The study recommended that SME owners should have positive perception of the usefulness of ICT, find alternative way of using ICT, source for adequate fund and acquire better ICT knowledge to have better chance of ICT adoption in Kogi State.